Empowerment and Entrepreneurship On WeChat: A focus on shared stories of Muslim women entrepreneurs in China - Zheng, Xin; Wan Noordin, Wan Norban (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
New media entrepreneurship has become the most popular business model today. This study demonstrates the motivations and strategies of Muslim women entrepreneurship on WeChat. Using a qualitative approach, data were obtained from eight female entrepreneurs in Yiwu, China, through in-depth interviews to enable the women to voluntarily and earnestly express their stories and experiences in entrepreneurial activities. The interview results were then analyzed using thematic analysis. Findings revealed that Muslim women's motivations for venturing into WeChat business entrepreneurship were mainly attributed to increasing family income, following their entrepreneurial education background, and the idea that it is a simple operation and involves low investment, making it an accessible and potentially lucrative business model. Other findings include how they promote the products mainly through relationship building and friendship. Challenges in doing business were also shared and explained in the findings. By showing the actual situation of Muslim women entrepreneurship in China and how WeChat enables these women to be empowered and form relationships to strengthen their business activities, this study provides deep insights for practitioners and academics. To cite this article (7th APA style): Zheng, X. & Noordin, W. N. W. (2023). Empowerment and entrepreneurship on WeChat: A focus on shared stories of Muslim women entrepreneurs in China. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(2), 85-95. https://doi.org/10.36782/jcs.v13i2.2473